Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $$\rho_\nu := res_{s=1} \zeta_K,\nu(s)=lim_{s\to 1}(s-1)\zeta_{K,\nu}(s)=\frac{2^r(2\pi)^s}{\omega_K |disc(\mathfrak(O)_K)|^{\frac{1}{2}}} \textrm{ (*)}$$

how can I follow that

$$\rho := res_{s=1} \zeta_K(s) = \rho_{\nu} * h_K = lim_{s\to 1}(s-1)\zeta_K(s) \textrm{ ?}$$

First the definitions:

$h_K = $ the number of elements in $mathscr{C}_K$ $\zeta_K(s) = \sum\limits_{\nu\in\mathscr{C}_K} \zeta_{K,\nu}(s)$, whith $\mathscr{C}_K$ the ideal class group of the number field $K$.
$\zeta_{K,\nu}(s)=\sum\limits_{I\in\nu}N(I)^{-s}$, $N$ the absolute norm.

I know the property (*) and I saw the second property in this paper: in Theorem 2 on page 3.

If I consider $res_{s=1}\zeta_K(s)=\rho_\nu * h_K = lim_{s\to 1}(s-1)\zeta_{K,\nu}(s) * h_K$.
But I don't see why $\zeta_{K,\nu}(s)*h_K$ should be $\zeta_K(s)$.

I would be happy if someone could help me with it.
All the best, Luca

share|cite|improve this question
up vote 1 down vote accepted

It's not true that $h_K \zeta_{K, \nu}(s) = \zeta_K(s)$.

It is true, however, that their residues are equal. This is true because $\zeta_K(s) = \sum_\nu \zeta_{K, \nu}(s)$, each $\zeta_{K, \nu}(s)$ has residue $\rho_\nu$ (which is independent of $\nu$ by the formula ($*$)), and there are $h_K$ terms in the sum.

share|cite|improve this answer
OK! So $res_{s=1}\zeta_K = res_{s=1}\zeta_{K,\nu}(s)*h_K = lim_{s\to 1}(s-1)\zeta_{K,\nu}(s)*h_K$. But how do I see then that $res_{s=1}\zeta_K = lim_{s\to 1}(s-1)\zeta_K(s)$ as in the paper, and not $= lim_{s\to 1}(s-1)\zeta_{K,\nu}(s)*h_K$? And thanks for the quick reply! – Luca Dec 9 '13 at 21:37
@Luca What is your definition of the residue? In any case, it shouldn't even matter as long as you can see that the residue is linear: $\text{Res }\zeta_K = \text{Res }\sum \zeta_{K, \nu} = \sum \text{Res } \zeta_{K, \nu} = \sum \rho_\nu = h_K \rho_\nu$ (where the last equality uses the fact that the $\rho_\nu$'s are all equal)... – Bruno Joyal Dec 9 '13 at 21:41
We defined the residue for $\zeta_K$ with the formula (*) times $h_K$. I'm sorry, but I still don't see how I have then $res\zeta_K = lim(s-1)\zeta_K(s)$. I only get $res\zeta_K = h_K * lim(s-1)\zeta_{K,\nu}(s)$ with what you write... how can I conclude that this equals $lim(s-1)\zeta_K(s)$? – Luca Dec 9 '13 at 22:13
@Luca That is the definition of the residue: – Bruno Joyal Dec 9 '13 at 22:16
It is? Ohhh.... than everything is clear :D Thanks a lot for your patience and explanation! – Luca Dec 9 '13 at 22:27

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.